Peran Bursa Efek Dalam Mendorong Pertumbuhan Ekonomi Sumatera Utara - Arnida Wahyuni Lubis; Mela Nurwansyah (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2020)
The Stock Exchange is a market that deals with the buying and selling of securities of companies that are already listed on the exchange. The capital market as one of the institutions that mobilizes public funds by providing means or places to carry out securities transaction activities. Economic growth is the growth of output (national income) caused by the natural increase of the population growth rate and saving rate.The purpose of the research carried out is to determine the role of the Indonesian Stock Exchange in encouraging economic growth in North Sumatra and to find out what factors affect economic growth in North Sumatra in the Capital Market sector. The method used in research is field research and documentation.The phenomenon of the role of the Indonesian Stock Exchange in encouraging economic growth in North Sumatra (North Sumatra) is still relatively low. Because many are still unfamiliar with financial products that are beneficial to the community. So far the people of North Sumatra mostly only know products in the form of savings in banks. such as the stock market and financial investment are still less desirable and understood. In 2016, only 1.25% of Indonesia's population had access to the capital market, while in 2016 it was 63.63% in banking. As a result, economic growth in North Sumatra through the stock exchange has decreased. Factors that influence economic growth are: human resources, natural resources, capital and technological mastery. Human resources in North Sumatra are qualified in science, skills and mindset of the people. As a result, economic growth in northern Sumatra increased. Natural resources in northern Sumatra are sufficient in their ability to use and preserve, as a result economic development has increased. Capital in northern Sumatra in the development of investment and labor expertise is less developed, consequently poverty has increased and economic growth has declined. Technology mastery in North Sumatra is sophisticated but to increase the effectiveness and efficiency of production. As a result theeconomy increased.